J. Mayone Stycos. Ideology, faith and family planning in Latin America : studies in public and private opinion on fertility control. Nueva York, [N.Y.] : McGraw-Hill Book Company, 1971. 418 p. - Keller, Allan (Estudios Demográficos y Urbanos, 1972)
J. MAYONE STYCOS, Ideology, Faith and Family Planning in Latin America. Studies in Public and Private Opinion on Fertility Control, Nueva York, McGraw-Hill Book Company, 1971.